Efficacy of a Combined Treatment of Botulinum Toxin and Intensive Physiotherapy in Hereditary Spastic Paraplegia - Paparella, Gabriella; Vavla, Marinela; Bernardi, Lisa; Girardi, Giulia; Stefan, Cristina; Martinuzzi, Andrea (Frontiers in Neuroscience, 2020)
Introduction The Hereditary Spastic Paraplegia (HSP) is a heterogeneous group of neurodegenerative disorders characterized by progressive spasticity and lower limbs (LL) weakness. There is no treatment to cure or halt the disease, except for symptomatic therapy. The use of botulinum toxin type A (BoNT-A) is one of the primary treatment for focal spasticity. Physiotherapy (PT) can help in maintaining residual functioning. We performed a retrospective study to evaluate the effect of the combined BoNT-A and intensive PT in patients with HSP. Methods Eighteen adult patients (50% females) with clinical diagnosis of HSP were recruited. Eleven patients had a genetic diagnosis of SPG4, 5, 7, 8, 11, 72. Patients were all autonomously deambulant or needed support. BoNT-A was injected in 36 LL in different spastic muscles under electromyographic guidance and followed by intensive PT sessions. Outcome measures included disease severity, motor functional measures, perceived pain self-report and quality of life. Assessments occurred at baseline, 1 and 3 months after BoNT-A injection. Results Most inoculated muscles were hamstrings, rectus femoris and gastrocnemius. We observed an improvement in muscle tone, in the gait velocity and distance length. Spastic Paraplegia Rating Scale was significantly reduced after treatment, in addition to improving pain and quality of life. These results were riconfirmed in 3 months time. Conclusion Our study indicates that combined treatment of BoNT-A and PT can lead to improvement of spasticity and quality of life in patients with HSP.